Understanding the Lord's Resistance Army insurgency - Dolnik, Adam; Butime, Herman (Insurgency and terrorism series (formerly known as Imperial College Press Insurgency and Terrorism Series ;, 2017)
Understanding the Lord's Resistance Army Insurgency provides a concise overview of the LRA, which has, for almost 30 years, conducted untold atrocities across the central African nations of Uganda, Southern Sudan, the Democratic Republic of the Congo and the Central African Republic. Written to fill a gap in academia in relation to African- and Christianity-based terrorism, this book is suitable for students, researchers and practitioners in political sciences, war, conflict and terrorism studies, African politics and international relations and development.